Presentist Social Functionalism: Bringing Contemporary Evolutionary Biology to the Social Sciences - Schulz, Armin W.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book presents and defends a new approach towards social functionalism: Presentist Social Functionalism. This approach draws on recent developments in evolutionary biology and philosophy of biology to provide a more compelling theoretical foundation for functionalist social analysis. Functionalist approaches to the social sciences$1 (Bwhich aim at using facts about what social institutions are for to provide a fulcrum with which to understand, evaluate, and respond to social reality$1 (Bare about as old as the subject itself, but have also been the subject of much criticism. In particular, a widespread concern for the functionalist tradition in the social sciences is that functional ascriptions often lack a plausible theoretical grounding, and that where such a theoretical grounding can be provided, the empirical presuppositions of this grounding often fail to be met. However, recent developments in evolutionary biology and the philosophy of biology promise to change this situation: they show that functional ascription can be compellingly made in an ahistorical, non-reproduction-based, and non-normative manner, which makes it possible to develop a new account of social functionalism that can fulfil the latter$1 (Bs theoretical and empirical desiderata. To show this, the book begins by laying out the major existing accounts of social functionalism and detailing their challenges. It then develops the new, alternative account of Presentist Social Functionalism. Given its interdisciplinary nature and application-focused approach, the book is of interest to researchers in a variety of fields, from evolutionary biology to the social sciences and philosophy.s
Chapter 1. The Theoretical Backbone$1 (BSocial Institutions, Functionalism, and Social Science -- Chapter 2. Missing Mechanisms, Arbitrary Assignments, and Counterfactual Conundrums$1 (BExisting Accounts of Social Functionalism and Their Problems -- Chapter 3. Presentist Social Functionalism$1 (BThe Foundations -- Chapter 4. Presentist Social Functionalism and the Function of Corporations -- Chapter 5. Institutional Corruption$1 (BThe Presentist Social Functionalist Account -- Chapter 6. Artifacts$1 (BA Presentist Social Functionalist Account (co-written with Clint Hurshman) -- Chapter 7. Conclusion.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Biology -- Philosophy; Evolutionary developmental biology; Philosophical anthropology; Anthropology; Philosophy of Biology; Evolutionary Developmental Biology; Anthropological Theory